2017
DOI: 10.18632/oncotarget.15848
|View full text |Cite
|
Sign up to set email alerts
|

NCTD promotes Birinapant-mediated anticancer activity in breast cancer cells by downregulation of c-FLIP

Abstract: Second mitochondria-derived activator of caspases (SMAC) mimetics is a class of new anticancer agents. However, most cancers exhibit de novo or acquired resistance to SMAC mimetics, posting a problem for broad applications in clinic, and highlighting the necessity of exploring combinational strategies to circumvent SMAC mimetic-resistance. We here showed that Norcantharidin, a drug that is currently being used in cancer treatment, significantly enhanced SMAC mimetic Birinapant-mediated cell viability inhibitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Studies have revealed that c-FLIP could inhibit apoptosis mediated by death receptors trough binding to Fas-associated death domain and inhibit caspase-8 activation (42). Overexpression of c-FLIP has been revealed in different types of cancers (26,43). c-FLIP upregulation has also been observed in gastric cancer tissues and cells (44).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have revealed that c-FLIP could inhibit apoptosis mediated by death receptors trough binding to Fas-associated death domain and inhibit caspase-8 activation (42). Overexpression of c-FLIP has been revealed in different types of cancers (26,43). c-FLIP upregulation has also been observed in gastric cancer tissues and cells (44).…”
Section: Discussionmentioning
confidence: 99%
“…New findings have provided evidence that c-FLIP can be regarded as a critical target for therapeutic intervention due to its inhibition in transcription and post-transcription (21,22). Increased expression of c-FLIP has been found in cell lines from various types of cancers, including colorectal (21,22), head and neck (23), prostate (24), cervical (25), breast (26), lung (27) and hepatocellular cancers (28), and c-FLIP has been demonstrated to be an important indicator in these types of cancers. In our study, we evaluated the roles and underlying mechanisms of miR-218 in human colon cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…cFLIP is a well-described negative regulator of cell death in many tumor entities and treatment strategies. cFLIP has been shown to protect from Smac mimetic-induced cell death [ 20 , 21 ] and silencing of cFLIP was found to sensitize different tumor cell lines to Smac mimetics [ 21 , 22 ]. Also, there are several reports showing that cFLIP can protect cancer cells from TRAIL-, CD95- or chemotherapy-induced cell death [ 23 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…In 2017, it was reported that a synergistic combination of SM BV6 and bortezomib effectively triggers cell death in B-cell non-Hodgkin lymphoma cells, even when apoptosis is blocked [126]. In addition, the combination of birinapant with norcantharidin (NCTD) was reported to promote anticancer activity in breast cancer cells [127]. Of note, some SMs were reported to be able to reverse resistance to chemotherapy agents by inducing cell death depending on the cell lines.…”
Section: Combined With Chemotherapymentioning
confidence: 99%